Cloning and expression analysis of a transcription factor gene BoWRKY2 from broccoli - Jiang Ming; Chen Beibei; Guan Ming; Li Jinzhi; Huang Xiaomei; Gu Yunji (浙江大学学报. 农业与生命科学版)
Broccoli (Brassica oleracea var. italica) , which belongs to Cruciferae family, is a cash crop widely cultivated in China, and it is regarded as one of the most consumed vegetables in the world. The flower head of broccoli is rich in minerals, vitamins, fibers as well as anti-oxidants, so it is recognized as a healthy vegetable with anti-cancer properties. As a major broccoli production center in China, the average plantation areas reach to 8 000 hm2 in Taizhou of Zhejiang Province. However, broccoli cultivation suffered from plant diseases of downy mildew and stalk break which were caused by Hyaloperonospora parasitica and Sclerotinia sclerotiorum, respectively, resulting in yield and quality loss.WRKY transcription factors played important roles in plant stress responses, and WRKY domains were defined as an approximately 60-amino acid motif named WRKYGQK as well as a zinc finger structure of C-X4-5-C-X22-23-H-X1-H at their C-terminus. The WRKY domain binds specifically to DNA sequence of (T) (T) TGAC (C/T) known as the W-box which exists in defense-related promoters. Enhanced disease resistance by overexpression of WRKY genes in different crop plants has been reported in recent years.In this study, a WRKY gene designated as BoWRKY2, was isolated from B. oleracea var. italica. Based on sequence analysis, expression patterns of BoWRKY2 were detected using reverse transcription-polymerase chain reaction (RT-PCR) method while challenged by H. parasitica and S. sclerotiorum, respectively.The results showed that the genome DNA sequence was 1 507 bp in length with two introns and a complete coding sequence of 987 bp, and the length of two introns were 425 and 95 bp, respectively; BoWRKY2 encoded 328 amino acids with a WRKYGQK residue and a zinc finger structure of C-X5-C-X23-H-X1-H. The WRKY domain located between 247 and 313 residues, and several DNA binding sites were found at sites of 66, 67, 69, 71, 74, 281, 282, 283 and 317. The WRKY domain was similar to that of oilseed rape with only one amino acid residue difference between them. Phylogenetic analysis indicated the BoWRKY2 was grouped with other Cruciferae plants such as B. napus, Arabidopsis thaliana, A. lyrata, Capsella rubella and Eutrema salsugineum, with 97% confidence. RT-PCR results revealed that the BoWRKY2 was induced by both H. parasitica and S. sclerotiorum with similar expression patterns. The expression level both increased at 6 h and 12 h, and decreased after 24 h, indicating the resistance responses of BoWRKY2 against two plant fungi.In a word, the cloning and expression analysis of BoWRKY2 gene lay the foundation for further studies in gene function identification and molecular breeding of broccoli.